Policing and the poetics of everyday life - Wender, Jonathan M. (University of Illinois Press, 2008)
Introduction: The bureaucratic paradox -- Division I -- Approaching human beings as problems -- The common roots of bureaucratic policing and mainstream social science -- The approach of a phenomenological aesthetics of encounter -- Division II -- Domestic violence encounters : the eye of the painter and the eye of the police -- The policing of childhood : encounters with juveniles -- The poetry of policing : encounters from the drug war -- Encountering the drama of mental and emotional crisis -- Policing death : the problematization of mortality -- Policing and the poetics of everyday life -- Postscript: Imagining otherwise